“Toda mulher em liberdade é um perigo”: a Pia União das Filhas de Maria no município de Nova Trento-SC - Facchini, Elis (2019)
The Pia Union of the Daughters of Mary was an institution connected to the Catholic Church with the intent to congregate single women, promoting Christian virtues and preserving purity with the protection of the Virgin Mary and Saint Agnes. The research accomplished two major objectives: to preserve the memory of women who participated in this entity, in the municipality of Nova Trento, State of Santa Catarina, especially between the years 1902 and 1964, during which the entity was active, investigating those ladies and their descendants, and to show how the Daughters of Mary absorbed the principles of the repressive Catholic morality and submitted to the Church control, but at the same time they found ways to infringe some rules, to challenge them and to take advantage of the space of socialization that the meetings and other activities meant. Thus, the research has entered into the ambiguous world of religion. We used three methods of analysis: documentary, searching for more detailed information in the books of the minutes and in the manual of the association; field research, through semi-structured interviews with open questions, initiated after prior approval of the Research Ethics Committee, and informed oral consent of the interviewed and the interviewer. Four interviews were conducted with women - former participants of the referred institution, and one man, the Italian sociologist Renzo Maria Grosselli; and, finally, the bibliographical, in the areas of Religion Science (Religion Studies), Gender, Sociology, History, Philosophy and Psychology. We also used the resources offered by the content analysis method to examine the material. In conclusion, we can affirm that we found a strict discipline that deeply affected the daughters of Mary’s lives in their family, and in their emotional and social dimensions. However, even in the face of these complex relationships, they found loopholes to transgress the rules to which they were subjected. That is a very contradictory and at the same time interesting scenario: at times, the participants of that association thoroughly complied to all the rules established by the Catholic Church, which was their social and meeting space, and at other times they opted for the transgression of the rules and took control of their autonomy